ORAL AND WRITTEN FEEDBACK ON INDONESIAN EFL STUDENTS' WRITING - Reti Wahyuni, - (2018)
Despite numerous studies on the area of feedback have been conducted, no final agreements have been made to evoke positive impacts and to detemine which the best type of feedback in EFL writing is. To answer the ongoing debate concerning which type of feedback is the best to overcome EFL students' problems in writing, oral feedback provides students with more chances to negotiate and clarify with their teacher about their writing and it is assumed as an alternative to written feedback. The present study aims to reveal the impacts of oral and written feedback on students' writing, students' grammatical accuracy and students' responses to feedback. This study employed a true experimental design. A mixed-method approach that combined qualitative and quantitative research method was used. By employing a cluster random sampling, 138 students from one senior high school in Bandung participated as the sample and involved in two experimental groups and one control group. The data were collected through students' scores and grammatical errors in writing recount texts through writing task I, writing task II and revised drafts. The questionnaire and interview section were used to explore students' responses. The results revealed that the feedback provision has its effectiveness and oral feedback is considered as the most effective feedback in the long term and written feedback as the most effective feedback in the short term of students' revised drafts. It also envinces that both experimental groups make statistically significant improvement in their writing compared to the control group. Moreover, the numbers of grammatical errors reduced from writing task I to writing task II as the result of feedback treatment. The students' responses varied in regard to all aspects of the questionnaire which overall were affirmative although some were revealed as negative. The findings of this study provide further evidence in support of the significant impacts of corrective feedback especially oral feedback which is applicable, interactive and beneficial. It is recommended that future studies focus on aspects involving individual differences and teachers' viewpoint.;-- Meskipun sudah banyak penelitian yang dilakukan tentang feedback, belum ada persetujuan tentang dampak positif dari feedback dan tipe feedback terbaik pada keterampilan menulis dalam bahasa Inggris sebagai bahasa asing. Untuk menjawab perdebatan yang berlangsung terus-menerus berkaitan dengan feedback untuk menyelesaikan permasalahan siswa dalam menulis, feedback lisan memberikan siswa kesempatan lebih untuk bernegosiasi dan klarifikasi tulisan mereka dengan guru dan feedback lisan dianggap sebagai sebuah alternatif dari feedback tertulis. Penelitian ini bertujuan untuk menemukan dampak dari feedback lisan dan tertulis pada tulisan siswa, ketepatan tatabahasa siswa dan respon siswa terhadap feedback dalam menulis. Penelitian ini merupakan penelitian eksperimen. Sebuah pendekatan mixed-method yang menggabungkan metode penelitian kualitatif dan kuantitatif digunakan. Dengan mengimplementasikan cluster random sampling, sebanyak 138 siswa sekolah menengah atas (SMA) di Bandung berpartisipasi sebagai sampel penelitian dan terbagi menjadi 2 kelompok eksperimen dan 1 kelompok kontrol. Data penelitian dikumpulkan melalui nilai-nilai siswa dan kesalahan-kesalahan siswa dalam menulis pada tugas menulis I, tugas menulis II dan revisi. Kuisioner dan wawancara digunakan untuk mengetahui respon siswa. Hasil penelitian memperlihatkan bahwa feedback memiliki efektivitas dan feedback lisan merupakan yang paling efektif untuk jangka waktu lama serta feedback tertulis adalah yang paling efektif pada proses revisi. Hasil penelitian menunjukan bahwa dua kelompok ekperimen memperoleh peningkatan yang signifikan dibandingkan dengan kelompok kontrol. Selain itu, jumlah kesalahan tatabahasa siswa mengalami penurunan dari tugas menulis I dan tugas menulis II sebagai hasil dari perlakuan pemberian feedback. Respon siswa beragam pada semua aspek dalam kuisioner dimana secara keseluruhan positif, meskipun beberapa respon negatif ditemukan. Penemuan penelitian ini memberikan fakta lebih jauh yang mendukung dampak signifikan dari feedback, terutama pada feedback lisan yang bisa diterapkan, interaktif dan bermanfaat. Penelitian ini merekomendasikan studi lanjut yang berfokus pada aspek mencangkup perbedaan individu dan sudut pandang guru.